Landscape Resilience and Inclusive Empowerment through Social Innovation in the Matano Village: Matano Iniaku Community Development Program - Rizki Pratiwi; Sainab Husain Paragay; Ahmad Syahrial Semen Dawai; Muhammad Nafiudin (Prospect Publishing, 2026)
The Matano Iniaku social innovation program integrates social innovation and landscape resilience approaches as a conservation-based community empowerment strategy in the Lake Matano area, South Sulawesi, Indonesia. This study aims to examine the implementation and the social, economic, and environmental impacts of the program using the Sustainable Livelihoods approach. This framework encompasses the strengthening of various livelihood assets, including natural capital, human capital, social capital, financial capital, and physical capital. The implementation results indicate that transforming agricultural systems from monoculture practices toward polyculture agroforestry has not only enhanced the adaptive capacity of local communities but also expanded economic opportunities for vulnerable groups through income diversification and the development of environmentally based enterprises. Furthermore, the program has contributed to ecosystem restoration, strengthened social capital, and enhanced collective awareness of the importance of conserving the Lake Matano area. This study highlights that social innovation grounded in multi-stakeholder collaboration can simultaneously strengthen social, economic, and environmental resilience. Nevertheless, the program's sustainability remains influenced by corporate support, local institutional capacity, government policies, and market dynamics that affect the continuity of community-based enterprises.